Entrepreneurship and MSMEs during the COVID-19 Health Emergency in Indonesia - Rizky Ilhami; Willya Achmad (ijd-demos, 2022)
AbstractThe purpose of this study is to demonstrate the challenges faced by MSMEs and entrepreneurship in Indonesia in dealing with the COVID-19 health emergency. Paying attention to market dynamics, regulatory framework, entrepreneurial vision and support from the Government. In addition, it seeks to identify new tools and strategies that companies have implemented to be able to sustain themselves in their business with the help of digital marketing and transformation of their products, to meet consumer needs quickly and thereby promote the reactivation of the country's economy. This research uses a qualitative approach with descriptive methods in analyzing the research data.Keywords: Entrepreneurship, MSMEs, COVID-19. AbstrakTujuan dari penelitian ini adalah untuk menunjukkan tantangan yang dihadapi oleh UMKM dan kewirausahaan di Indonesia dalam menghadapi darurat kesehatan COVID-19. Memperhatikan dinamika pasar, kerangka regulasi, visi kewirausahaan dan dukungan dari Pemerintah. Selain itu, ia berupaya mengidentifikasi alat dan strategi baru yang telah diterapkan perusahaan untuk dapat mempertahankan diri dalam bisnis mereka dengan bantuan pemasaran digital dan transformasi produk mereka, untuk memenuhi kebutuhan konsumen dengan cepat dan dengan demikian mendorong pengaktifan kembali ekonomi negara. . Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif dalam menganalisis data penelitian.Kata kunci: Kewirausahaan, UMKM, COVID-19.